2016
DOI: 10.1007/978-3-319-32152-3_23
|View full text |Cite
|
Sign up to set email alerts
|

Parallelising the Computation of Minimal Absent Words

Abstract: International audienceAn absent word of a word y of length n is a word that does not occur in y. It is a minimal absent word if all its proper factors occur in y. Minimal absent words have been computed in genomes of organisms from all domains of life; their computation also provides a fast alternative for measuring approximation in sequence comparison. There exists an O(n)-time and O(n)-space algorithm for computing all minimal absent words on a fixed-sized alphabet based on the construction of suffix array (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…It was also shown that the set of all MAWs of y is sufficient to uniquely reconstruct y [13,15]. Several linear-time and linear-space algorithms have been proposed to compute the set of MAWs for constant-sized [13,26,17,5,2,3] or integer [16,8] alphabets. These algorithms are based on text indexing data structures such as suffix tree, suffix array or ✩ A preliminary version of this paper was presented at the 21st International Symposium on Fundamentals of Computation Theory (FCT 2017) [12].…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the set of all MAWs of y is sufficient to uniquely reconstruct y [13,15]. Several linear-time and linear-space algorithms have been proposed to compute the set of MAWs for constant-sized [13,26,17,5,2,3] or integer [16,8] alphabets. These algorithms are based on text indexing data structures such as suffix tree, suffix array or ✩ A preliminary version of this paper was presented at the 21st International Symposium on Fundamentals of Computation Theory (FCT 2017) [12].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the LWI across the word y for a pattern x, we need to compute the set of minimal absent words in a sliding window of size m = |x| of y. Several linear-time and linearspace algorithms have been proposed to compute the set of minimal absent words [10,6,3,4,15]. Ota et al presented an on-line algorithm that requires linear time and linear space [28].…”
Section: Introductionmentioning
confidence: 99%
“…3. Our technique could serve as a basis for a new parallelization scheme for constructing antidictionaries (see also [27]), in which several documents are processed concurrently.…”
Section: Final Remarksmentioning
confidence: 99%